Effectiveness of E-Procurement Policy in Procurement Planning at the Public Works and Spatial Planning Departmentof Baubau City - Unidayan, Marjan; Islamy, La Ode Syaiful; Andriani, Rininta (Program Studi Ilmu Pemerintahan, 2026)
This study examines the effectiveness of the e-procurement policy in the procurement planning stage at the Public Works and Spatial Planning Office (PUPR) of Baubau City. The study is significant since procurement planning serves as the foundation for achieving efficiency, transparency, and accountability in public spending, as mandated by LKPP Regulation No. 11 of 2021. The objective is to evaluate the extent to which the e-procurement policy achieves effectiveness across six key activities: needs identification, determination of goods/services types, procurement methods, work packaging, scheduling of goods/services utilization, and budget management. Employing a qualitative method with a phenomenological approach, the study explores experiences, perceptions, and challenges of stakeholders through interviews, observations, and policy document analysis. The findings reveal a misalignment between procurement plans and realization in 2023–2024, with 22% of packages experiencing contract delays. The main contributing factors include low technical literacy in using the Electronic Procurement System (SPSE), weak integration of asset data and technical documents, and delays in revising Detail Engineering Designs. Although the financial absorption rate is relatively high (99.17%), administrative and technical shortcomings hinder smooth implementation. In conclusion, the effectiveness of e-procurement policies is highly dependent on data accuracy, human resource capacity, and procedural consistency. Therefore, strengthening digital literacy and monitoring systems is crucial for optimizing regional procurement.